Đánh giá kết quả điều trị triệu chứng trong ung thư vú giai đoạn muộn - Châu , Cao Khả; Hiệp , Phạm Như; Tùng, Nguyễn Đình; Thọ , Võ Thế; Tường, Phạm Nguyên; Aí, Nguyễn Thanh; Duy , Phan Cảnh; Khoa, Trần (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.